Crystal structure and computational studies of N-((2-ethoxynaphthalen-1-yl)methylene)-4-fluoroaniline - Atalay, Sehriman; Macit, Mustafa; Bulbul, Hakan (European Journal of Chemistry, 2021)
The Schiff base compound, N-((2-ethoxynaphthalen-1-yl)methylene)-4-fluoroaniline, has been synthesized and characterized by X-ray diffraction method. The title compound, C19H16FNO, crystallizes in triclinic, space group P-1 (no. 2), a = 10.6343(9) Å, b = 11.4720(10) Å, c = 13.8297(13) Å, α = 102.466(7)°, β = 104.763(7)°, γ = 98.972(7)°, V = 1552.7(2) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.086 mm-1, Dcalc = 1.255 g/cm3, 24355 reflections measured (3.16° ≤ 2Θ ≤ 51°), 5779 unique (Rint = 0.0794, Rsigma = 0.0696) which were used in all calculations. The final R1 was 0.0373 (I > 2σ(I)) and wR2 was 0.0763 (all data). The title compound contains two molecules with a similar structure in the asymmetric unit cell. The packing of the crystal structure is determined by weak C–H···F and C-H···N intermolecular hydrogen bonds. The contributions of these weak interactions in the crystal structure were calculated by the Hirshfeld surfaces and examined by the intermolecular interactions within the structure. The existence, nature and percentage contribution of different intermolecular interactions H···H, C···H, N···H, and F···H were determined using Hirshfeld surface analysis and fingerprint plots.